(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The estuary is a mixing area between the mass of fresh water and seawater, which causes substances in the bottom waters to rise to the surface so that nutrient concentrations become high. Research on estuary water mass confluence still needs to be carried out, especially regarding the turbidity front estuary. So far, this research is limited to in situ data. Therefore, remote sensing technology is trying to be applied to detect turbidity front estuary. This study aims to develop local TSS algorithms and detect turbidity fronts based on Sentinel-2 satellite imagery. This research method uses Sentinel-2 imagery to determine the turbidity front boundary based on TSS compared to in situ salinity data and TSS as data validation. The results of this study show that the empirical algorithm obtained from the band ratio (red/(blue+green+red)) on Sentinel-2 has the best results with a determination coefficient (R2) = 0.7409. The results of satellite imagery show that the turbidity front estuary occurs at a distance of 1,4 – 3 km, while the in situ data occurs at a distance of 2 – 4 km at the Bengawan Solo estuary. There is a difference in the TSS value of 1.9182 mg/L between the in situ data and satellite imagery in the turbidity front estuary area. Seasonal conditions, rainfall and tides affect the concentration and distance of the turbidity front from the river mouth.